Phylogenomics resolves the etiology of dieback disease and deciphers Ceratocystis dalbergicans sp.nov., causal agent of Dalbergia sissoo decline - Haq, Imran Ul; Ijaz, Siddra; Latif, Muhammad Zunair; Khan, Iqrar Ahmad; Ali, Hayssam M.; Kaur, Sukhwinder (Frontiers in Genetics, 2023)
Dalbergia sissoo is one of the most economically important trees in forestry, agroforestry, and horticulture. This tree species is severely threatened by dieback. Widespread dieback outbreaks and infestations have drastically destroyed billions of D. sissoo trees. Hence, we attempted to resolve the dieback etiology through phylogenomics associated with D. sissoo mortality. The Ceratocystis species was evaluated using morphologically investigated fungal isolates collected from dieback-affected tissue plants. Based on the symptomatology, we have differentiated dieback from Fusarium wilt and concluded that the Ceratocystis fimbriata sensu lato complex is causing shisham dieback in Pakistan. As the Ceratocystis species complex is a cryptic species complex, we used genomics and phylogenetic analysis for deciphering its evolutionary hierarchical order. The pathogen’s operational taxonomy was unlocked with the help of phylogenomics, and it was discovered that isolates from D. sissoo represent a species distinct from the other species in the C. fimbriata sensu lato species complex. The name Ceratocystis dalbergicans sp. nov. has been given to the fungus causing dieback disease in D. sissoo.